READABILITY AND COMPATIBILITY OF CLASS VIII SUBSTANCE PRESSURE MATERIALS WITH SCIENCE PROCESS SKILLS CATEGORIES - Faola Firnanda; Laily Rosdiana (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
This study aims to determine the readability and suitability of material pressure class VIII with the category of science process skills. The research method used is descriptive research with a qualitative approach. The results of this study indicate that the suitability of the books for science class VIII students with science process skills is 60% in the appropriate category. Aspects of science process skills contained in the book include skills of observation, classification, interpretation, using tools or materials, applying concepts, and communicating. Meanwhile, the results of the readability of the VIII grade students' science book on substance pressure, the average value was 3 in the good category. From the research that has been carried out, it can be concluded that the science student's book on substance pressure material is in accordance with the SPS aspect. Suggestions from researchers, the books used by students should contain all aspects of science process skills. By adding SPS aspects that have not been presented in the book, which include predicting skills, asking questions, hypothesizing skills, and planning an experiment.